Managing in the gray : five timeless questions for resolving your hardest problems at work - Badaracco, Joseph (Boston, Massachusetts : Harvard Business Review Press, 2016)
It's a manager's job to make the tough calls, but the hardest part of being a manager is resolving those "gray areas"--situations where analysis of the numbers, facts, and data fails to provide a clear answer. These gray areas test not only a manager's skills, but their humanity. You have to choose, commit, and act, and to live with the consequences. Harder still, you have to be able to explain yourself and your decisions to others. How do you get it right, both as a manager and as a human being? Bestselling author Joseph Badaracco presents a five-question framework that helps people balance the analytical side of being a manager with the human side and find an answer when analysis falls short: (1) What are the net, net consequences? (2) What are my core obligations? (3) What will work in the world as it is? (4) What do we really stand for? and (5) What is my best judgment and best self? Managing in the Gray reflects and distills the timeless wisdom of many of the most powerful, penetrating, and noble minds throughout history--philosophers ranging from Aristotle to Nietzsche, religious leaders like Confucius and Jesus, political thinkers like Thomas Jefferson, even poets and artists--and is a powerful guide to managers for resolving their toughest problems at work, the ones that keep them up at night.--
Tools for judgment -- What are the net, net consequences? -- What are my core obligations? -- What will work in the world as it is? -- Who are we? -- What can I live with?.
Includes bibliographical references (pages 159-179) and index.
Print version record.
Keywords: Management -- Philosophy; Problem solving; Management -- Philosophy; Problem solving; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books